HUBUNGAN TINGKAT PENGETAHUAN KOMUNIKASI TERAPEUTIK MAHASISWA KEPERAWATAN DENGAN PENILAIAN SIKAP PADA MATA KULIAH PKK MAHASISWA SEMESTER VIII STIKES MEDISTRA INDONESIA: THE RELATIONSHIP BETWEEN NURSING STUDENTS' THERAPEUTIC COMMUNICATION KNOWLEDGE LEVELS WITH ATTITUDE ASSESSMENT IN THE VIII SEMESTER STUDENT PKK COURSE STIKES MEDISTRA INDONESIA IN 2022 - Eva Julianti Nurali; Lisna Agustina; Baltasar S.S Dedu (Akademi Keperawatan Yarsi Samarinda, 2023)
Attitude in nursing is called an important determinant of behavior, the attitude that exists in a person will give a picture of a person by knowing a person's attitude will be able to predict how the response or action will be taken by the person to a problem. So that this attitude is important for communication in nursing is called therapeutic communication. The existence of a communication in nursing can minimize the occurrence of errors or misunderstandings in the nursing process. Attitude assessment needs to be based on the knowledge of therapeutic communication, obtained since becoming a nursing student. But in fact nursing students are still found to have poor therapeutic communication attitudes.Research purposes : This study aims to determine the relationship between the level of knowledge of nursing students' therapeutic communication with attitude assessment in the VIII semester student PKK course of STIKes Medistra Indonesia.Research methods : The research used is quantitative, analytical observational research design and using a cross sectional approach. The population is nursing students in the VIII semester PKK course STIkes Medistra Indonesia in 2022 totaling 133 students with a sample of 100 respondents. Data collection technique using simple random sampling.Research result : It was found that with a significant level or value of , p value was 0.000 < value 0.05, there was a correlation between Therapeutic Communication Knowledge and attitude assessment in the PKK course for Nursing Students in Semester VIII STIKes Medistra Indonesia in 2022.Conclusion : There is a Relationship between Knowledge of Therapeutic Communication and attitude assessment in the PKK course by Nursing Students in Semester VIII of STIKes Medistra Indonesia in 2022.